2014
DOI: 10.1590/s1677-5538.ibju.2014.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of permanent memotherm urethral stent in the treatment of recurrent bulbar urethral strictures

Abstract: Purpose: To evaluate the long term outcomes of permanent Memotherm urethral stent in the treatment of recurrent bulbar urethral stricture. Materials and Methods: Twenty patients who underwent permanent Memotherm urethral stent implantation due to recurrent bulbar urethral stricture following previous unsuccessful surgical procedure from 1996 to 2002 were included in the study. Long--term outcomes of the patients were evaluated. Results: The overall success rate was 87.5% at the end of the tenth year. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
2
5
0
3
Order By: Relevance
“…migration, discomfort, incontinence, infection and encrustation. Indeed, Atesci et al ( 8 ) reported high complication rate of permanent Memotherm ® urethral stent in recurrent bulbar urethral strictures (discomfort in implantation area: 40%, partial stent migration: 10%, stone formation in implantation area: 10% and dripping after micturition: 75%). They also found that the overall success rate of permanent urethral stents was 87.5% at the end of the tenth year.…”
Section: Discussionmentioning
confidence: 99%
“…migration, discomfort, incontinence, infection and encrustation. Indeed, Atesci et al ( 8 ) reported high complication rate of permanent Memotherm ® urethral stent in recurrent bulbar urethral strictures (discomfort in implantation area: 40%, partial stent migration: 10%, stone formation in implantation area: 10% and dripping after micturition: 75%). They also found that the overall success rate of permanent urethral stents was 87.5% at the end of the tenth year.…”
Section: Discussionmentioning
confidence: 99%
“…Various management modalities of urethral stricture disease, such as internal urethrotomy, intermittent urethral dilatations, and open urethroplasties, have been well described in the literature [2,3,7]. However, clear curative roles of these interventions are still underway with unimpressive rates of success.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent recurrence after initial treatment is common [2]. Urethral stent implantation has been categorized as a minimally invasive technique that can be safely and effectively used as a primary surgical procedure to treat recurrent urethral stricture [3]. According to the American Journal of Roentgenology, temporary stent placement has been considered the treatment of choice in cases of recurrent urethral strictures.…”
Section: Introductionmentioning
confidence: 99%
“…Бужирование уретры, как изолированное, так и в сочетании с другими процедурами и в качестве метода послеоперационного предотвращения рецидивов, используется до сих пор [1][2][3]. Систематический обзор Jackson M.J. et al (2014) [2] включал данные наблюдения за 776 пациен-тами. Было отмечено снижение числа рецидивов у пациентов, которым выполняли бужирование уретры в сравнении с пациентами, которым не выполняли (ОР 0.70, 95% ДИ 0,48-1,00).…”
Section: эндоуретральные методы лечения стриктур уретры у мужчинunclassified
“…Установка уретрального стента, по данным Atesci et al (2014), является высокорезультативным методом с эффективностью до 87,5% с периодом наблюдения до 12 лет и сопровождается низкой частотой осложнений [5].…”
Section: эндоуретральные методы лечения стриктур уретры у мужчинunclassified